2012
DOI: 10.1007/s10393-012-0787-1
|View full text |Cite
|
Sign up to set email alerts
|

Hay Fever in a Changing Climate: Linking an Internet-Based Diary with Environmental Data

Abstract: Investigating the impact of climate change on human health requires the development of efficient tools that link patient symptoms with changing environmental variables. We developed an internet-based hay fever diary linked to simultaneously recorded pollen load and weather variables in Canberra, Australia over spring 2010. We recruited 42 hay fever sufferers to complete a simple online pollen diary daily over a period of 60 days. In conjunction, daily airborne pollen load was counted and meteorological data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Because that study was a patient-based study, only seriously ill individuals were included; however, even small amounts of pollen scattering were believed to induce reactions. Medek et al (2012) reported a daily symptom investigation of 42 hay fever patients and the pollen relationship with the daily climate using a web-based survey. Their study clarified the daily nasal rhinoconjunctivitis symptoms of patients and the pollen load via a web investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Because that study was a patient-based study, only seriously ill individuals were included; however, even small amounts of pollen scattering were believed to induce reactions. Medek et al (2012) reported a daily symptom investigation of 42 hay fever patients and the pollen relationship with the daily climate using a web-based survey. Their study clarified the daily nasal rhinoconjunctivitis symptoms of patients and the pollen load via a web investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[4]; Medek et al . [18]). Note that data from secondary stations in Darwin (Palmerston), Canberra (Holder) and Auckland (Grafton Museum) are not included in the numerical analysis in this paper.…”
Section: Methodsmentioning
confidence: 99%
“…Allergic rhinoconjunctivitis is a seriously debilitating disease leading to poor quality of life and reduced productivity aa well as contributing to other complications including asthma exacerbations (Walls et al 2005, Bousquet et al 2008, Meltzer et al 2009. Airborne grass pollen levels have been positively correlated with symptoms of allergic rhinoconjunctivitis and anti-histamine use in patients with grass pollen allergy (Johnsen et al 1992, Johnston et al 2009, Medek et al 2012. Allergic sensitisation to grass pollen can precede the development of allergic asthma in children (Hatzler et al 2012) and airborne levels of grass pollen are associated with hospital admissions for asthma (Erbas et al 2007a, Darrow et al 2012.…”
Section: Context Of the Australian Aerobiology Working Group Researchmentioning
confidence: 99%